Studying the Microbiome: “Omics” Made Accessible - O'Toole, Paul W.; Flemer, Burkhardt (Seminars in Liver Disease, 2016)
The term microbiome refers to the collection of microbes or microbial genes in a specified location or clinical sample. Identifying micro-organisms has historically relied upon bacteriological culture, which is time consuming and difficult to effectively implement. The recent adaptation of culture-independent techniques for profiling microbial communities, allied with next-generation massively parallel DNA sequencing, allows clinician scientists to determine the entire microbial content of a specimen to a forensic level of detail within 48 hours. The technology is still young, and the main thrust of current efforts is to identify how changes in the microbiome covary with a variety of syndromes and diseases, and to determine if these changes are causative or consequential. Regardless of the outcome of these investigations, it is already apparent that the gut microbiome is a useful biomarker for intestinal and extraintestinal disease. In this review, the authors summarize the main concepts in microbiome analysis, and prospects for the microbiome's clinical deployment.
Keywords: microbiome; microbiota; intestinal disease